DINAMIKA KELOMPOK TANI CEMPAKA DI KELURAHAN MERAS KECAMATAN BUNAKEN KOTA MANADO - Novtrianto Makawekes; Lyndon R.J. Pangemanan; Melsje Y. Memah (Universitas Sam Ratulangi, 2016)
ABSTRACTThe aims of this study to understand dynamic the Cempaka Farmers Group, the studied fromelements of group dynamics that is, goal of group, structure group, task function, building and groupdevelopment, compactness group, atmosphere group, pressure group, effectiveness of group, and hiddenpurpose. This study has been conducted since February 2016 untill May 2016 at the Cempaka FarmerGroup in Meras Village Bunaken Sub-distric Manado Municipality.Retrieval and data collectionincluded primary data and secondary data. Primary data was obtained from a member of the FarmersGroup using by a questionnaire, direct interview and observation in the research location. Secondarydata were obtained from various print and online media as well from journals and literature relating tothis study. Data analysis methods applied in this study, using by Likert Scale and Descriptivemethods.The research result showed that the Dynamics of Cempaka Farmers Group categorizeddynamic. It was because group dynamic elements going well.Key Word: Dynamics, Farmers Group